2017
DOI: 10.1007/s00299-017-2209-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic N-glycoproteome analysis of maize seedling leaves during de-etiolation using Concanavalin A lectin affinity chromatography and a nano-LC–MS/MS-based iTRAQ approach

Abstract: The identification of N -glycosylated proteins with information about changes in the level of N -glycosylation during de-etiolation provides a database that will aid further research on plant N -glycosylation and de-etiolation. N-glycosylation is one of the most prominent and abundant protein post-translational modifications in all eukaryotes and in plants it plays important roles in development, stress tolerance and immune responses. Because light-induced de-etiolation is one of the most dramatic developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…To perform a deep analysis of the maize proteome and phosphoproteome during de-etiolation, the first leaves of etiolated 7-day-old maize seedlings (B73 inbred) were illuminated with white light and harvested at 0 h, 1 h, 6 h and 12 h for mass spectrometry analysis ( Figure 1 ). We chose these samples for analysis because in our previous studies [25, 31, 32] we found that the first leaves of 7-day-old etiolated maize seedlings showed no significant changes in growth compared with light-grown seedlings when subjected to illumination for 12 hours, and few proteins involved in development and growth were found to be differently expressed when comparing the proteomes of etiolated and normal leaves. Moreover, the etiolated leaves turned green after 12 hours of illumination, which indicated that processes related to greening in leaves were completed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To perform a deep analysis of the maize proteome and phosphoproteome during de-etiolation, the first leaves of etiolated 7-day-old maize seedlings (B73 inbred) were illuminated with white light and harvested at 0 h, 1 h, 6 h and 12 h for mass spectrometry analysis ( Figure 1 ). We chose these samples for analysis because in our previous studies [25, 31, 32] we found that the first leaves of 7-day-old etiolated maize seedlings showed no significant changes in growth compared with light-grown seedlings when subjected to illumination for 12 hours, and few proteins involved in development and growth were found to be differently expressed when comparing the proteomes of etiolated and normal leaves. Moreover, the etiolated leaves turned green after 12 hours of illumination, which indicated that processes related to greening in leaves were completed.…”
Section: Resultsmentioning
confidence: 99%
“…The maize inbred line B73 was used in this study. The seedlings were planted and samples were collected as described previously [32]. Under the same conditions, two biological replicates were performed and the first seedling leaves from each replicate were rapidly sampled.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations